The Implementation of Indonesia's 2013 Curriculum Using a Scientific Approach at State Elementary School - Fertikasari, Gita (Nur Science Institute, 2024)
Background: The aims of this study is 1) to know the implementation of 2013 Curriculum by using scientific method in SD Negeri 01 Pretek Batang, 2) to know the difficulties faced by the teacher in arranging teaching learning material curriculum 2013 in SD Negeri 01 Pretek Batang, 3) to know the teacher’s solution to face the difficulties in arranging teaching learning material curriculum 2013 in SD Negeri 01 Pretek Batang. Method: The kind of this research was qualitatif research. Collecting data technique was interview, documentation, and observation. The data analysis was interactive, the validity data was used triangulation which consists of source triangulation and technique triangulation. Result: The result of this study shows that 1) the the implementation of 2013 Curriculum by using scientific method in SD Negeri 01 Pretek Batang related to the observing, questioning, consuming, brainstorming and communicating concept. In the concept there are PAIKEM and discussion. 2) the difficulties faced by the teacher in arranging teaching learning material curriculum 2013 in SD Negeri 01 Pretek Batang was not existed, because the teacher get used to with it and they have experience by the method that was used Implication: The implications of this study show that teachers have strong competencies in implementing the 2013 Curriculum, with minimal obstacles encountered during the learning process. Furthermore, the use of a humanistic and contextual approach enhanced emotional connection with students and increased the relevance of the learning material. Novelty: This study highlights the implementation of the scientific approach across multiple grade levels in a single primary school and demonstrates teachers' ability to independently adapt nationally standardized materials to local contexts.